Tectonic setting, rock chemistry, and metamorphism of an Archean gabbro–anorthosite complex, Tessiuyakh Bay, Labrador - Wiener, Richard W. (Canadian Journal of Earth Sciences, 1981)
The Tessiuyakh gabbro complex, an Archean complex of layered ultramafic, gabbroic, and anorthositic gneisses, has been discovered at Tessiuyakh Bay, Labrador. The complex is similar to Archean metamorphosed gabbro and anorthosite in Greenland and contains relict plagioclase phenocrysts and graded igneous layering, and has an olivine tholeiitic composition.The earliest recognized deformational features in the gabbro complex are isoclinal folds with axial plane metamorphic foliation. Thrust faults parallel to the foliation formed during the latter stages of isoclinal folding. The isoclinal folds and thrust faults are refolded by an open, south-southeast-plunging anticline, and all the above structural features are cut by undeformed, 2.4 Ga granite.Metamorphism associated with the early isoclinal folds attained amphibolite to granulite facies. The orthopyroxene "isograd" is largely a function of Mg/(Mg + Fe) in metamorphosed gabbros. A continuous hornblende breakdown reaction to orthopyroxene, augite, plagioclase, and oxide occurs in metamorphosed gabbros with [Formula: see text], whereas more Mg-rich gabbros lack orthopyroxene. Origin as oceanic layered gabbro is suggested for Archean gabbro–anorthosite complexes.